Preparação e caracterização de células solares de Perovskita CH3NH3PbI3 a partir do Pb reciclado de baterias automotivas de chumbo-ácido - Silva, Paulo Victor Soares e (2017)
Perovskite-based ceramic materials have long been the target of scientific research because of their remarkable electrical and optical properties. Recently such materials have gained even more attention because of the discovery of their ability to act as a substitute for the electrolyte in dye sensitized solar cells (DSS). Since then, perovskite has become one of the protagonists in the search for solar cells of high efficiency and of lower cost than those based on silicon. Among the compounds studied in this category of material stands out Methylammonium lead halide (CH3NH3PbI)which presents a promising photovoltaic performance and low production cost. Pb has its main use in the automotive battery industry which, despite legislation, does not recycle any material used during the manufacturing process. This leads to a potentially damaging to the environment accumulation due to metal toxicity. This, coupled with the imminent market entry of lithium-ion automotive batteries, leads to a scenario of large quantities of unused Pb in the coming years. Sensitive to this issue, the work presented here aims to obtain and analyze CH3NH3PbI perovskite, from Pb recovered from discarded automotive batteries for further use in perovskite solar celss. The metal contained in the electrodes of the battery (in the form of PbO2 and metallic Pb) is extracted and subjected to a sequence of chemical and thermal processes in order to become the precursor PbI2. This is then deposited by spin-coating on glass substrates already coated with fluorine-doped tin oxide and titanium dioxide followed by reaction with the CH3NH3I organic solution to give the title compound. The synthesized PbI2 had an X-ray diffraction pattern in agreement with the standard spectrum. The obtained ceramic material showed a very characteristic optical behavior, with a well-defined UV-Vis absorption spectrum, with a wide range of absorption. The bandgap, calculated by the tauc method, was 1.46 eV, being in agreement with the literature. However, porosity of the material shown by SEM was different from that which is in agreement with what is found in the literature.